A novel Ag3PO4/Nb2O5 fiber composite with enhanced photocatalytic performance and stability. Issue 123 (27th November 2015) - Shao, Ruyi; Zeng, Xi; Cao, Zhenzhu; Dong, Hongjie; Wang, Liying; Wang, Fang; Liu, Jinrong; Li, Zhi; Liang, Qinghua
Abstract : A novel Ag3 PO4 /Nb2 O5 fiber composite was fabricated through depositing Ag3 PO4 nanoparticles on wrinkled Nb2 O5 fiber surfaces through a facile depositing precipitation approach. Abstract : A novel Ag3 PO4 /Nb2 O5 fiber composite was fabricated through depositing Ag3 PO4 nanoparticles on Nb2 O5 fiber surfaces through a facile depositing precipitation approach. The as-prepared Ag3 PO4 /Nb2 O5 photocatalyst was characterized through XRD, SEM, XPS and UV-Vis measurements. SEM results show that biomorphic Nb2 O5 fibers have a wrinkled surface and porous walls. The special morphology of the Nb2 O5 fibers provided a large amount of voids and interfaces in favor of decorating with Ag3 PO4 nanocrystals. The Ag3 PO4 /Nb2 O5 composite photocatalyst exhibits much higher photocatalytic activity for the degradation of rhodamine B than pure Ag3 PO4 under simulated sunlight. Such superior photocatalytic activity is mainly attributed to enhanced visible light absorption and effective separation of photogenerated electron–hole pairs derived from the Ag3 PO4 /Nb2 O5 heterojunction. No loss of photocatalytic activity has been observed after four recycles. Moreover, the large size of the Ag3 PO4 /Nb2 O5 composite allows it to be easily separated from the solution.